Object operations and objects communication in the object-oriented programming education - Donchev, I. P.; Todorova, E. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Unfortunately, in the academic literature on object-oriented programming (OOP) we notice adverse tendency to focus attention mainly on language-specific syntax constructions and static description of the data used, at the expense of processes dynamics in the program, operations with objects and communication between them, which we believe is the key to mastering this paradigm. To improve the learning process, in this article we propose some basic concepts, needed for a successful OOP course; classification of the object operations, conformable with the course objectives as well as some specific recommendations for teachers.